2004
DOI: 10.1111/j.1525-1594.2004.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Adsorption of Homocysteine Using an HFR‐ON LINE Technique

Abstract: HFR-ON LINE (double chamber HDF with reinfusion of ultrafiltrate regenerated through a charcoal-resin cartridge) is a novel method which combines the processes of diffusion, convection, and adsorbance. We have investigated the effect of such a treatment on the homocysteine (Hcy) levels in ten patients with a mean Hcy level of 57.6 micromol/L (range 24.1-119.7 micromol/L). We have measured the Hcy, folate, and vitamin B12 predialysis and postdialysis, and in the ultrafiltrate precartridge and postcartridge at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…As mentioned previously, Ragazzoni et al [24 ]and De Simone et al [25] showed a significant sparing in essential, branched and total amino acids during HFR compared to on-line HDF. Furthermore, as described by Splendiani et al [27], the resin is capable of adsorbing significant amounts of homocysteine, while limiting adsorption of vitamin B 12 or folate. The characteristic sparing of vitamin C (Morosetti [26]) by HFR is of importance due to its established action on use and handling of blocked iron deposits, unlike other types of HDF, where loss of this vitamin has been reported [28,29,30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, Ragazzoni et al [24 ]and De Simone et al [25] showed a significant sparing in essential, branched and total amino acids during HFR compared to on-line HDF. Furthermore, as described by Splendiani et al [27], the resin is capable of adsorbing significant amounts of homocysteine, while limiting adsorption of vitamin B 12 or folate. The characteristic sparing of vitamin C (Morosetti [26]) by HFR is of importance due to its established action on use and handling of blocked iron deposits, unlike other types of HDF, where loss of this vitamin has been reported [28,29,30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…54 In terms of plasma amino acid levels, no significant changes in their intradialytic levels occur during hemofiltrate reinfusion (HFR), whereas a ~25% reduction occur during acetate-free biofiltration. 55 A number of clinical studies on patients with ESRD have revealed that HFR remarkably improve dialytic efficiencies and solute removal, such as the removal of uremic marker molecules (β2M, leptin, and free immunoglobulin light chains), [56][57][58] cardiovascular risk factors (homocysteine), 50 inflammatory cytokines (C-reactive protein [CRP], interleukin [IL]-1, and IL-6), and biomarkers of oxidative stress (oxidized low-density lipoprotein and IL-1β). 58,59 In a comparison between HFR and online HDF, both were found to be highly biocompatible and to considerably reduce inflammatory markers, such as CRP and IL-6.…”
Section: Paired Filtration Dialysis With Endogenous Hemofiltrate Reinmentioning
confidence: 99%
“…In addition, because uncaptured small molecules can be removed by diffusion at the hemodialyzer, the regenerated ultrafiltrate is successfully applied as replacement fluid. 48 Adsorption capacities were further increased by combining hydrophobic styrene-based resin along with uncoated charcoal, because the resin has a high binding affinity for several midmolecular-weight species, such as β2M 49 and homocysteine, 50 or free immunoglobulin light chains. 51 The other benefits of this regenerated ultrafiltrate include a better acid-base balance due to the reinfusion of endogenous bicarbonate 52 and also the considerable advantage of combining high convection without physiologic molecule loss.…”
Section: Paired Filtration Dialysis With Endogenous Hemofiltrate Reinmentioning
confidence: 99%
“…Trace elements, such as manganese, selenium, arsenic, cadmium, mercury, lead, chromium, and zinc, also remain unaltered after passing through the adsorbent column, whereas copper is completely retained by the charcoal (de Francisco et al, 1997). Adsorption capacities were further increased by combining hydrophobic styrenic resin along with uncoated charcoal, because the resin has a high binding affinity for several mid molecular weight species, such as, 2M (Marinez de Francisco et al, 2000) and homocysteine (Splendiani et al, 2004), or free immunoglobulin light chains (Testa et al, 2010). The other benefits of this regenerated ultrafiltrate include a better acid-base balance due to the reinfusion of endogenous bicarbonate (de Francisco et al, 1997), and also the not inconsiderable advantage of combining high convection without compromising physiologic molecule loss.…”
Section: Paired Filtration Dialysis With Endogenous Reinfusion (Hfr)mentioning
confidence: 99%
“…In terms of plasma amino acid levels, no significant changes in their intradialytic levels occur during HFR, whereas a ~25% reduction occur during acetate-free biofiltration (Borrelli et al, 2010). A number of clinical studies on ESRD patients have revealed that HFR remarkably improve dialytic efficiencies and solute removal over a wide molecular weight ranges, such as, the removal of uremic marker molecules ( 2M, leptin and free immunoglobulin light chains) (Bolasco et al, 2006, S. Kim et al, 2009, Testa et al, 2006, cardiovascular risk factors (homocysteine) (Splendiani et al, 2004), inflammatory cytokines (CRP, IL-1, IL-6), and biomarkers of oxidative stress (ox-LDL, IL-1 ) (Calo et al, 2011, Testa et al, 2006. In a comparison between HFR and on-line HDF, both were found to be highly biocompatible and to considerably reduce inflammatory markers, such as, CRP and IL-6 (Panichi et al, 2006).…”
Section: Paired Filtration Dialysis With Endogenous Reinfusion (Hfr)mentioning
confidence: 99%